Proposing Jagani Tradition of Buton as a Convergent Cultural Intervention for the Demographic Dividend - Fajrin R, Hasina; Biopsi Puji Hastuti, Heksa; ., Rahmawati; ., Syaifuddin (KnE Social Sciences, 2023)
Indonesia is estimated to face a demographic dividend in the next few years. The Indonesian government had programmed demographic dividend convergence in various domains, including the health sector. The stunting derivation program was strongly associated with the first 1000 days. We recommended a strategy for initiating convergence through the jagani tradition. This tradition was the potential to be a medium of intervention to achieve a positive demographic dividend for several reasonable arguments. First, the aspect of time was the moment of marriage which is considered a sacred moment marking the union of two persons to form a family. Second, the element of the actor leading the ritual, bhisa, is culturally highly respected because it impacts a bride‘s married life. Third, the speech in the jagani tradition contained household guidance materials covering various dimensions of life. These three aspects complemented each other in delivering messages for forming quality families and accomplished generations. The adjustment of the jagani verbal message convergently touched potential targets: the new families of prospective parents of the next generation. Internalization converges at the beginning through the jagani tradition. Keywords: jagani tradition, Indonesian demographic dividend, convergence, cultural intervention